Sustainable Design Elements In The Building Conservation Policy In Malaysia - Yahaya, Shaiful Rizal Che (2020)
The integration of Sustainable Design Elements (SDEs) and Practices into building conservation works would bring environmental, social and economic benefits whilst retaining its historical values. However, any intervention to historic buildings must adhere to the principles of building conservation which poses a challenge to ensure its historic values are protected whilst addressing the contemporary needs such as SDEs and statutory requirements. Currently, there is a lack in the present guidelines in Malaysia’s Jabatan Warisan Negara (JWN) that integrates SDEs and Practices into the building conservation works. Without proper guideline, the integration SDEs and Practices into building conservation works may not be holistic. This research aims to propose the SDEs and Practices suitable to be integrated into JWN’s guidelines on building conservation. This research has three objectives. Objective 1 was achieved through documentary analysis, in which 60 SDEs and Practices items were identified and grouped into five main categories. Interview session has been conducted with 26 respondents for achievement of objectives 2 and 3. It is discovered that these SDEs and Practices had already been practiced voluntarily in some of the building conservation works to some various degrees and at some various conservation works stages. This shows that these SDEs and Practices have large potential to be fully adapted and adopted into JWN’s building conservation guidelines. Incorporating these SDEs and Practices into the existing guidelines for conservation works will provide guidance to architects, building conservators and other stakeholders in promoting a greener and sustainable practice of building conservation works in Malaysia.